THE UNQUALIFIED RIGHT OF ACCESS TO COMPANY RECORDS BY NON-HOLDERS OF THE COMPANY’S SECURITIES UNDER SOUTH AFRICAN COMPANY LAW Nova Property Group Holdings Ltd v Cobbett (MandG Centre for Investigative Journalism NPC as amicus curiae) 2016 (4) SA 317 (SCA) - Vela Madlela (Obiter, 2019)
This note, therefore, discusses the Nova case with a focus on the approach of the court regarding the proper interpretation and the ambit of the right of access to a company’s records by any person as conferred by section 26(2) of the Companies Act 71 of 2008. It provides some critical comments on the main issues that this judgment raises, including the impact of the Constitution in this area of South African company law, the interpretation of section 26(2) in light of the role and impact of companies in society, the interpretation of section 26(2) in light of the purposes of the Companies Act 71 of 2008, the interface between section 26(2) and PAIA as well as the potential for abuse of the right of access to company records enshrined in section 26(2). This is followed by some concluding remarks.